Local content expert-assigned Taxonomy with Library of Congress Subject Headings (LCSH): a comparative analysis / Eza Eliana A Wahid and A’dillah Mustafa - A Wahid, Eza Eliana; Mustafa, A’dillah (Faculty of Information Management, 2024)
Taxonomy is a classification system that helps researchers conceptualize phenomena based on their dimensions and characteristics. It is an integral process involving a high complexity in understanding a subject classification. This paper aims to represent an update for the taxonomy development of Sports Science and recreational; it contributes to the prescriptive knowledge of taxonomy design and seeks to augment both rigorous taxonomies building and evaluation, including a comprehensive analysis of the expert-assigned keywords with a comparison to Library of Congress Subject Headings. This study employs comparative subject analysis as the methodology for comparing expert-assigned keywords with LCSH. The analysis will identify the similarities and differences in the classification of the taxonomy used in the UiTM Local Content Hub. The subjects used in Sports Science & Recreational Digital Collection in PTAR Local Content Hub are very minimal compared to the structured classification of subjects in the classification web.